BUILDING A HEALTHY AND PROSPEROUS COMMUNITY THROUGH THE SYNERGY OF VILLAGE-OWNED ENTERPRISES AND THE MERAH PUTIH COOPERATIVE - Hyronimus Se; Avianita Rachmawati; Yohana Christina (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2026)
Strengthening village economic institutions is essential to sustainably managing local potential. Cooperatives and Village-Owned Enterprises (BUMDes) share the same goal of improving community welfare, yet they often operate in isolation, limiting their potential for synergy. This community service program aimed to enhance the management capacity of BUMDes and the Merah Putih Cooperative through managerial support and the development of a participatory synergy model. The activities were conducted in Maurole Subdistrict, Ende Regency, using lectures and interactive discussions. The results showed improved understanding among administrators in business and financial management, as well as increased awareness of the importance of institutional collaboration. The synergy between BUMDes and cooperatives represents a strategic step toward building an inclusive and sustainable village economy. The program also encouraged administrators to develop more structured and realistic business plans. In addition, participants gained a better understanding of transparency and accountability in financial management. The discussions provided space to share experiences and address existing challenges. The established collaboration is expected to strengthen the competitiveness of village enterprises. With continuous mentoring, village economic institutions can develop more professionally and independently.